Holy Scripture as a Polemical Tool in “Contra legem sarracenorum” Riccoldo da Monte di Croce - Dawczyk, Maciej (Phantom of Muhammad, Shade of Samuel Byzantine Empire in Relation to Members of Other Cultures and Religions (7th–15th c.): No. XXXIX, 2020)
Old and New Testaments were used by Riccoldo da Monte di Croce (in Contra legem sarracenroum) for the critique of literary layer of Qur’an. Additionally, the author tried to use them for proving immorality of Islam and the false of its dogmas. Furthermore, in the final part of the treatise, the author focused not on using the Scripture for the critique of Islam but on affirmation of Gospel on its own and proving its superiority to Qur’an.